2020
DOI: 10.5539/jas.v12n4p77
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of No-till Farming on Durum Wheat Mycorrhization in a Semi-Arid Region: A Long-Term Field Experiment

Abstract: Maintaining a reliable and sustainable agricultural production system has become one of the major concerns of producers in arid and semi-arid regions. Simplifying farming techniques and practicing Direct Seedling (DS) could contribute to insure the sustainability of agriculture, preserving the natural resources and the environment. Direct Seedling based on limiting soil plowing has a potential number of benefits, including reduced production costs and soil erosion. Associated with the organic mulch, this techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…Results obtained are in agreement with those of Roldán et al [77], who observed the highest levels of mycorrhizal propagules in the no-till soil compared to tillage soils. Taibi et al [78] observed an increase of durum wheat mycorrhization rate after 3-year adoption of NT in Algeria. NT practice causes less frequent soil disturbance and fungal hyphae have a greater opportunity to be developed with surface residue retention, thus promoting fungal abundance and diversity [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained are in agreement with those of Roldán et al [77], who observed the highest levels of mycorrhizal propagules in the no-till soil compared to tillage soils. Taibi et al [78] observed an increase of durum wheat mycorrhization rate after 3-year adoption of NT in Algeria. NT practice causes less frequent soil disturbance and fungal hyphae have a greater opportunity to be developed with surface residue retention, thus promoting fungal abundance and diversity [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…Bailey, et al, [40] Canola-wheat-barleybarley; canola-barleypea-wheat; canola-peaflax-barley 2,07 61 Kutcher, et al, [41] Saskatchewan, Rosthern 2007 4 Canola-wheat-wheat 1,98 12 Baan, et al, [42] Wheat-oilseed-wheat; fallow oilseed-wheat 2,66 17…”
Section: Merchouch 2018 15mentioning
confidence: 99%
“…Sorghum-winter wheatwinter wheat; maizesoybean-winter wheatwinter wheat 3,06 12 Carignano, et al, [57] Kansas, Tribune 1994 4…”
Section: 63 20mentioning
confidence: 99%